Formulation of Blended‐Lithium‐Salt Electrolytes for Lithium Batteries. Issue 9 (2nd December 2019) - Xu, Gaojie; Shangguan, Xuehui; Dong, Shanmu; Zhou, Xinhong; Cui, Guanglei
Abstract: Blended‐salt electrolytes showing synergistic effects have been formulated by simply mixing several lithium salts in an electrolyte. In the burgeoning field of next‐generation lithium batteries, blended‐salt electrolytes have enabled great progress to be made. In this Review, the development of such blended‐salt electrolytes is examined in detail. The reasons for formulating blended‐salt electrolytes for lithium batteries include improvement of thermal stability (safety), inhibition of aluminum‐foil corrosion of the cathode current collector, enhancement of performance over a wide temperature range (or at a high or low temperature), formation of favorable interfacial layers on both electrodes, protection of the lithium metal anode, and attainment of high ionic conductivity. Herein, we highlight key scientific issues related to the formulation of blended‐salt electrolytes for lithium batteries. Abstract : The right mix : Blended‐salt electrolytes have aroused great interest in the burgeoning field of next‐generation lithium batteries. This Review discusses the evolution of blended‐salt electrolytes with the aims of summarizing the key scientific issues related to their formulation and providing meaningful perspectives for their future development toward practical applications.